2016
DOI: 10.22302/jpk.v34i2.228
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Dan Kendala Dalam Penguatan Dan Penumbuhan Kelompok Pemasaran Bokar Terorganisir Di Provinsi Sumatera Selatan

Abstract: The organized marketing system has able to improve quality of raw rubber material and farmers ' share. Therefore, it K e y w o r d s : R a w r u b b e r m a t e r i a l ; strengthening; developing; organized marketing group AbstrakSistem pemasaran terorganisir telah mampu meningkatkan mutu bokar dan bagian harga yang diterima petani. Oleh karena itu, diperlukan pembinaan untuk memperkuat dan menumbuhkan sistem p e m a s a r a n t e r s e b u t d e n g a n mengidentifikasi kendala yang menghambat dan potensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
4
Order By: Relevance
“…These data show that many smallholders still sell through non-PMU channel, especially within the traditional marketing system. However, many studies have found that income, price, and efficiency of PMU marketing channel were more profitable for smallholders than non-PMU marketing channel Herdiansyah, Nurmalina, &Winandi, 2015;Husin, Yulius, Dessy, & Antoni, 2017;Sujarwo, 2015;Syarifa, Agustina, Alamsyah, &Nugraha, 2016). Therefore this study aims to provide answers to the following research question: Which factors mainly affect smallholders' choice of a PMU or non-PMU marketing channel ?.…”
Section: Problem Statementsmentioning
confidence: 98%
See 1 more Smart Citation
“…These data show that many smallholders still sell through non-PMU channel, especially within the traditional marketing system. However, many studies have found that income, price, and efficiency of PMU marketing channel were more profitable for smallholders than non-PMU marketing channel Herdiansyah, Nurmalina, &Winandi, 2015;Husin, Yulius, Dessy, & Antoni, 2017;Sujarwo, 2015;Syarifa, Agustina, Alamsyah, &Nugraha, 2016). Therefore this study aims to provide answers to the following research question: Which factors mainly affect smallholders' choice of a PMU or non-PMU marketing channel ?.…”
Section: Problem Statementsmentioning
confidence: 98%
“…For this group, it is needed guidance and extension about organized marketing and technical guidance in improving quality of rubber material. The most fundamental supporting factors in strengthening the marketing group is a fair dealing between management board and members of group, as well as the activities that were bonding the members, such as: savings and loans, and supplying inputs or groceries for farmers (Syarifa et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aturan KUD Berkat menyatakan bahwa jumlah bokar yang lebih dari 20% tidak diikusertakan lelang atau bokar ditawar dengan harga lebih rendah oleh pabrik. Petani menjual bokar ke para tengkulak karena terikat pinjaman dana untuk kebutuhan hidup (Syarifa, 2016).…”
Section: Sumber: Laporan Hasil Lelang Bokar Kud Berkat 2011-2016unclassified
“…Upaya perbaikan mutu bokar dapat terlaksana jika semua pihak seperti petani, pabrik, pedagang dan pemerintah daerah berkomitmen untuk menghasilkan dan memperdagangkan bokar bersih bermutu baik. Salah satu upaya untuk menghasilkan bokar bersih adalah dengan membentuk kelompok pemasaran bersama dengan pengawalan dari pemerintah (Syarifa, Agustina, Alamsyah, & Nugraha, 2016). Dengan adanya kelompok pemasaran bersama ini, petani dapat mengolah bokar bersih dengan menggunakan koagulan anjuran dan menjual bokarnya berdasarkan kadar karet kering (KKK) bukan berdasarkan penjualan berat basah seperti yang biasa diterima petani, sehingga petani akan mendapat harga yang lebih baik.…”
Section: Pendahuluanunclassified